Transforaminal Endoscopic Lumbar Discectomy versus Coblation Nucleoplasty Combined with Collagenase Chemonucleolysis for Lumbar Disc Herniation with Grade I Degenerative Spondylolisthesis - Yuyu Guo; Liuhu Han; Tingting Li; Bingbing Xu; Penghui Ke; Jun Hu; Rongyi Zhang; Yan Guo; Long Zhao; Likui Wang (Pain and Therapy)
Abstract Introduction To investigate the short-term clinical effect of transforaminal endoscopic lumbar discectomy (TELD) versus coblation nucleoplasty (CN) combined with collagenase chemonucleolysis (CCNL) in the treatment of lumbar disc herniation (LDH) with grade I degenerative spondylolisthesis. Methods From January 2019 to December 2020, 60 patients who had LDH with grade I degenerative spondylolisthesis were divided into two groups. Group A adopted TELD while Group B adopted CN combined with CCNL. The surgical efficacy was evaluated according to the visual analogue scale (VAS), oswestry disability index (ODI), quality of recovery-15 (QoR-15), and modified MacNab criteria. Imaging findings including lumbar lordosis (LL), segmental lordosis angle (SL), slip percentage (SP), and disc height (DH) were compared between the two groups pre-operation and at the last follow-up. Results VAS (back and leg), ODI, and QoR-15 were significantly decreased at each time point after operation in all groups. There were significant differences in VAS (back and leg), ODI, and QoR-15 between the two groups at 3 days post-operation (P < 0.05), VAS (leg), ODI, and QoR-15 at 3 months post-operative (P < 0.05), and QoR-15 at 6 months post-operative (P < 0.05). There was no significant difference in LL, SL, SP, and DH between the two groups at the last follow-up (P > 0.05). Conclusion Both the two operations can relieve the symptoms of lower back and leg pain in patients, and neither of the two operations caused further progress of lumbar spondylolisthesis. Compared with CN combined with CCNL, TELD had more significant improvement in early lower back and leg pain and shorter post-operative duration of hospitalization. Trial Registration The trial was registered on ClinicalTrials.gov (ChiCTR2300076809).